2020
DOI: 10.1002/cbic.202000681
|View full text |Cite
|
Sign up to set email alerts
|

Directed Evolution of a Cp*RhIII‐Linked Biohybrid Catalyst Based on a Screening Platform with Affinity Purification

Abstract: Directed evolution of Cp*RhIII‐linked nitrobindin (NB), a biohybrid catalyst, was performed based on an in vitro screening approach. A key aspect of this effort was the establishment of a high‐throughput screening (HTS) platform that involves an affinity purification step employing a starch‐agarose resin for a maltose binding protein (MBP) tag. The HTS platform enables efficient preparation of the purified MBP‐tagged biohybrid catalysts in a 96‐well format and eliminates background influence of the host E. col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…An iron-depleted minimal medium was used to avoid unwanted incorporation of FePPIX during the expression. , After cell lysis, 3 equiv of the MnPPIX cofactor were supplemented to form the ArM (typical scaffold protein concentrations were ∼20 μM in cleared lysates; Figure S3). Previously, ArMs were successfully immobilized on chromatography resins to streamline screening procedures. Therefore, the mixture was applied onto a Strep-Tactin resin and washed twice using a 96-well filter plate. Finally, the Strep-Tactin immobilized ArM variants were transferred into a transparent MTP and their peroxidase activity was determined using ABTS as the substrate and AcOOH as the oxidant.…”
Section: Resultsmentioning
confidence: 99%
“…An iron-depleted minimal medium was used to avoid unwanted incorporation of FePPIX during the expression. , After cell lysis, 3 equiv of the MnPPIX cofactor were supplemented to form the ArM (typical scaffold protein concentrations were ∼20 μM in cleared lysates; Figure S3). Previously, ArMs were successfully immobilized on chromatography resins to streamline screening procedures. Therefore, the mixture was applied onto a Strep-Tactin resin and washed twice using a 96-well filter plate. Finally, the Strep-Tactin immobilized ArM variants were transferred into a transparent MTP and their peroxidase activity was determined using ABTS as the substrate and AcOOH as the oxidant.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to Fe and Cu metalloenzymes, there are many ArMs that have employed other biologically relevant metal cofactors, such as V, Cr, Mn, ,, Co, , Ni, , Zn, and Mg, as well as those with abiological metal centers, including Ru, Rh, ,,, Pd, Os, Ir, ,,, and Au . These studies can be divided into two categories, namely those that target understanding native metalloenzyme functionality and those that aim to utilize the ArM scaffold to enhance the catalytic properties of organometallic complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Directed evolution was later applied to this system, and the T98H/L100K/K127E mutant was identified to increase the activity 2.2-fold. Interestingly, MD simulations suggested that all three of these residues are located opposite to the Rh metal center …”
Section: Beyond Fe and Cu: Insights Into The Secondary Coordination S...mentioning
confidence: 99%
See 1 more Smart Citation
“…34−36 A series of engineered variants of NB-1 generated via SSM were found to catalyze cycloaddition of acetophenone oxime (2a) and 1,4-dimethoxy-2-butyne (3a) via C(sp 2 )−H bond activation (Figure 1c). 36 However, these point mutations had only minor effects on the catalytic activity because the Cp*Rh(III) cofactor of NB-1 was largely exposed to solvent due to its shallow cavity. It was also speculated that the existence of an H 2 O molecule in the active-site limits the catalytic performance of the artificial metalloenzymes in general.…”
mentioning
confidence: 99%